Transformative impact of blockchain technology and smart contracts on dispute resolution: legal challenges and other implications. - Christie, David; Mante, Joseph; Mak, Charles Ho Wang (10th Kuwait International Law School annual international academic conference (KILAW 2024), 2024)
This paper comprehensively analyses the potential of blockchain technology and smart contracts to revolutionise dispute resolution. As dispute resolution methods evolve, blockchain and smart contracts, which offer efficiency, transparency, and fairness, are becoming more critical. That is especially the case in mediation and construction adjudication, which are less traditionally formal and tend to be carried through much more quickly than other forms of dispute resolution. The opportunity of blockchain comes from its ability to demonstrate a tamper-proof, clear record, reducing risks of misunderstanding and bias. This facilitates the transfer and verification of evidence both in the carrying out of projects and during dispute resolution processes. Smart–digital contracts with terms coded indirectly- allow for automated contract enforcement. They execute automatically upon meeting specific conditions. This automation brings a new efficiency level, cutting the time and costs of conventional dispute resolution. Nonetheless, integrating blockchain and smart contracts in dispute resolution faces several challenges. The current limited understanding and acceptance of these technologies in the legal sector is an imminent issue. Legislative changes are necessary to provide a solid legal framework for these technologies in legal processes and to address potential inconsistencies of approach. Such reform requires strong cooperation among lawmakers, technologists, and legal experts to ensure implementation that adheres to legal and ethical norms and ensures that the technologies can be applied with confidence by the stakeholders within the process. This collective effort is crucial for seamlessly integrating blockchain and smart contracts into legal frameworks.
Keywords: Blockchain technology; Dispute resolution methods; English law; Smart contracts

L'attractivité du droit OHADA - Akonumbo, Atangcho Nji; Monkam, Cyrille; Pironon, Valérie (Colloque ”L'attractivité du droit OHADA”, 2023)

The impact of blockchain and smart contracts on dispute settlement: a case for mediation. - Mak, Charles Ho Wang; Mante, Joseph (2023 TIAC Journal of international dispute settlement inaugural annual conference (TJIDS 2023), 2023)
The research is premised on two important developments, accelerating technological innovation and shifts in dispute resolution paradigms. These advancements offer an innovative framework for dispute avoidance and a more efficient, transparent process for resolving conflicts, particularly in commercial settings. To make this case, we use blockchain technology and smart contracts as technological exemplars, and mediation as an example of dispute resolution mechanism that can be positively impacted by the use of the relevant technology. The potential of these technologies to promote dispute avoidance and the emerging legal frameworks for resolving blockchain technology and smart contract disputes were also explored. We also examine how blockchain technology and smart contracts can be integrated into the mediation process, the advantages, challenges, and possible solutions.
Keywords: Blockchain technology; Dispute resolutions; Disputes; Smart contacts; Technological innovation

La dématerialisation des valeurs mobilières dans l'espace OHADA : regard juridique et prospective - N'Tchatat Tounya, Fabrice Léonel (Vers une économie résiliente, verte et inclusive, 2022)
Keywords: Dématérialisation; Dépositaire central; Société par actions; Valeurs mobilières

Les IDE en Afrique : les pays africains les plus attractifs et les secteurs les plus prometteurs - Iguergaziz, Wassila; Boulifa, Yamina (Les récentes tendances du commerce international et les défis du développement durable, 2019)
L'Afrique reste une destination privilégiée pour les investisseurs d’autres continents. Si le monde entier a le regard tourné vers l'Afrique, c’est en partie pour son taux de croissance de son PIB et de ses échanges internationaux. La part de l’Afrique dans les investissements directs étrangers (IDE) mondiaux est passée de 1,2 % en 2007 à 3,1 % en 2012. L’Afrique est l’une des rares régions à avoir enregistré une hausse des entrées d’IDE en 2011 et 2012 alors que les flux mondiaux baissaient sur la même période. A partir de là, nous dégageons la problématique suivante : quels sont les pays africains les plus attractifs pour les IDE et les secteurs les plus prometteurs ? Abstract: Africa remains a preferred destination for investors from other continents. If the whole world is looking to Africa, it is partly for its rate of growth of its GDP and its international trade. Africa's share in global foreign direct investment (FDI) increased from 1.2% in 2007 to 3.1% in 2012. Africa is one of the few regions to have experienced an increase in inflows of 'FDI in 2011 and 2012 while global flows decreased over the same period. From there, we highlight the following problem: which African countries are the most attractive for FDI and the most promising sectors?

Interaction entre les Cours de justice communautaires et les juridictions suprêmes nationales : spécificités de la Cour Commune de Justice et d’Arbitrage (CCJA) de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) - Ondo Mve, César Apollinaire (La diffusion de la jurisprudence des Cours suprêmes judiciaires francophones au temps d’internet, 2019)

Facteurs déterminants la comptabilisation des actifs immatériels par les dirigeants des entreprises de l'espace OHADA : cas du Togo - Koumagnanou, Komivi (2018)
The OHADA accounting framework is not immune from the choice of accounting policies for intangible assets. The need to make an accounting choice for intangible assets depends on a number of factors. This article aims to identify the motivations of managers in the choice of accounting for intangible assets. In a second step, we described the methodological approach of our work. Thus, we proceeded to the empirical study which is both qualitative and quantitative. The collected data was then analyzed. From the companies' case, it was found that the tax reasons, the accounting principles, the logic of obtaining the loans, the follow-up of the practice of the competitors, the implementation of the recommendations of audit, the sense of limiting the wage demands are pushing executives to make accounting choices for intangible assets.
Keywords: Accounting choice; Actif immatériel; Choix de comptabilisation; Intangible assets; OHADA

La normalisation comptable internationale par l’IASB - Danjou, Philippe (16ème colloque de l’ACN, 2017)
Cette note, préparée pour le 16ème colloque de l’ACN, a pour objet d’exposer de façon succincte les origines du mécanisme d’harmonisation internationale des normes comptables IFRS dans le secteur privé, les modalités de fonctionnement de l’organisme qui édicte ces normes, la façon elles sont transposées dans la règlementation. On y présentera l’état des lieux en matière d’adoption internationale. Enfin, le processus d’élaboration d’une norme IFRS sera illustré par un survol des travaux ayant abouti à la publication récente de la norme IFRS 16 « Contrats de location ».

The Application of CISG in International Arbitration - Cisár, Ivan (FIRST BRNO ARBITRATION CONFERENCE 2017, 2017)
International arbitration allows great flexibility of the parties to structure their whole relationship. One of the key factors is the choice of the law applicable to the substance of the relationship. CISG is intended for the regulation of such relations between international businessmen. This paper builds on the empirical evidence of the International Arbitration Surveys conducted among various groups of practitioners on their reasoning con cerning choice of law applicable to the substance of the relationship and argues that although CISG is not chosen by them frequently (or arguably not chosen at all), this “omission” is not warranted.
Keywords: CHOICE OF APPLICABLE LAW; CISG; INTERNATIONAL ARBITRATION

Les difficultés rencontrées par les PME lors de la mutation comptable PCGC/OHADA : étude exploratoire des PMEcongolaises - Diwavova, Justin Kamavuako; Mayimbi Ekuli Ngokana, Patrick (Problématique de la mutation comptable PCGC/OHADA dans les PME, 2016)
Cette communication a pour objectif d'appréhender les difficultés rencontrées par les PME congolaises à l'aube de la mutation comptable PCGC/OHADA et les facteurs qui les causent. L'enquête par questionnaire mené auprès d'un échantillon 99 PME opérant dans la partie Ouest de la RD Congo a permis de mettre en évidence deux faits saillants suivants : (i) la mutation comptable PCGC/OHADA s'implémente avec difficulté en contexte des PME. Ces difficultés sont plus ressenties lors des travaux d'inventaire (application difficile de la convention de la prééminence de la réalité sur la forme), dans la tenue des livres comptables (tenue manuelle, traitement approximatif des opérations sur la TVA) ainsi que dans la confection de certains tableaux de synthèse (notamment le TAFIRE); (ii) les facteurs de contingence structurelle (la taille de l'entreprise et son organisation comptable) et les facteurs de contingence comportementale (les profils de dirigeants et de teneur de livres comptables) se révèlent significativement comme étant les causes de ces difficultés.
Keywords: Facteurs de contingence; Mutation comptable; OHADA; PCGC; PME

Les difficultés de normalisation comptable dans l'espace OHADA - Bampoky, Boniface (38è Congrès de l'AFC, 2016)
A comprehensive history of African, Malagasy, Mauritian and from the Comoros accounting standards, has not yet been established to allow to make a summary of all the past and current difficulties arising from it and to propose the conditions for a suitable accounting standard normalization which backs up the development of the OHADA members states. Following a chronology which sums up the major historical facts based on the lack of accounting doctrine coming from the OHADA ground realities, the competent authorities are widely invited to give their opinions about the matter. History, as another research method in accounting and control, is concerned.
Keywords: Accounting doctrine; Accounting plan; Accounting standards; Doctrine comptable; Norme comptable; Plan comptable; SYSCOA; SYSCOHADA

De la pertinence informationnelle des chiffres comptables publiés par les sociétés cotées sur les Bourses d'Afrique de l'Ouest (B.R.V.M et Ghana Stock Exchange) - Casta, Jean-François; Mbengue, Alioune Badara (2016)
This paper examines the value relevance of accounting numbers published by listed companies on the markets BRVM (SYSCOHADA) and the GSE (IFRS). This study is part of the problem of the quality of accounting in emerging markets and of the current debate on the adoption of IFRS in the OHADA space. Through the methodology of the studies of associations, the results show: (1) The model (linear/non-linear) the most adequate for to write the relationship between accounting numbers and stock performance according to the indicator used; (2) The accounting earnings is more relevant on the BRVM by report to the GSE. And, the book value of equity is more informative on the GSE; (3) the effect of the presence of auditor(s) external(s) Big is not significant on this relationship.
Keywords: BRVM; GSE; IFRS; Référentiel SYSCOHADA; SYSCOHADA; Value-Relevance

The impact of non-operationalisation of the SADC protocol and international transport agreements on cross border road transport movement in the SADC region - Monyepao, Kaine (34th Annual Southern African Transport Conference 6-9 July 2015, 2015)
The failure by Sothern African Development Community (SADC) countries to fully implement the SADC Protocol on Transport, Communications and Meteorology (the Protocol) and bilateral agreements in regard to road transport negatively impacts the seamless movement of cross border road transport and significantly contributes to the challenges faced by the cross border industry as a whole. The full implementation of the Protocol in regard to road transport, and bilateral agreements would lead to efficient cross border transport regulation and transportation and in turn culminate in reduction of challenges facing the sector. This would lead to reduction of transportation costs, improvement in productivity, and accelerated growth in intra-regional trade, regional economic integration and overall SADC socio-economic development. This paper outlines the extent to which the provisions of the Protocol and bilateral agreements have been implemented by SADC countries and the key challenges emanating from the partial operationalisation of the instruments. The paper is based on findings from engagements with key government and private sector stakeholders in the regional transport environment and various research conducted by the C-BRTA between 2011 and 2014. The partial operationalisation of the instruments has resulted in disjointed regulatory frameworks and inability to: holistically address corridor constraints/ non-tariff barriers, facilitate seamless cross border movements, facilitate liberalisation of access to transport markets in the region, harmonise standards and procedures, and facilitate economic growth and trade between SADC countries. It is possible for the SADC region to realise the aspirations set out in the Protocol and bilateral agreements, and this paper outlines some of the solutions. To begin with, there is need for SADC countries to embrace the need to eradicate the existing self-centric regulatory approach limited to micro-needs and market protectionism. This would need to be underpinned by strong orientation towards the need to achieve macro benefits emanating from a regional perspective in regard to regulating cross border road transport movement. Taking off from this departure point, SADC countries can objectively establish a solid ground towards fully operationalising the Protocol and bilateral agreements. This paper outlines some of the interventions that can be implemented to ensure SADC countries fully operationalise the provisions of the Protocol on transport and bilateral agreements.
Keywords: Southern African Transport Conference; Transportation

Internal Audit Characteristics and Quality of Accounting Information in Nigeria - Ogundana, Oyebisi Mary; Ojeka, Stephen; Ojua, Michael; Nwaze, Chukwu (1st Academic Conference of Accounting and Finance, 2015)
The basic goal of Accounting is to provide enabling accounting information for reliable decision-making. The quality level of this accounting information comes from the company's governance practices, thereby emphasizing the importance of corporate governance in companies. Recently, following the financial crises resulting in accounting scandals, attention has been moving towards Internal Audit Function as an important factor in the structure of Corporate Governance. This paper therefore examined the extent of the relationship between internal audit function and the quality of accounting information of companies. The study adopted the Survey research design. The research instrument employed was Questionnaire which was administered to internal auditors of the “Big Four”. Linear regression analysis was employed in the analysis of the data collected with the use of Statistical Packages for Social Sciences (SPSS). The results revealed that there is a significant relationship between the internal audit characteristics and the quality of accounting information. It was recommended that in order to provide credibility to the financial statement, there should be a law in place mandating attachment of internal auditors report to the financial statement
Keywords: Accounting quality; Accounting report; Corporate governance; Fraud; internal auditing

Effets d'un usage d'ERP sur les pratiques comptables normées dans le contexte de l'OHADA - Bampoky, Boniface; El Bachir, Mouhamed (35ème Congrès de l'AFC, 2014)
Tested answers through the use of an exploratory approach (with IT experts in ERP and accounting users) are brought to the issue of the impact of ERP use on standardized accounting practices. The OHADA (Organization for the Harmonization of Business Law in Africa) was used as an adjunct to conduct the study. The classic business accounting is changing as well as the paradigm of accounting teaching. Some accounting standards increasingly disappear.
Keywords: Bookkeeping; Comptabilités normées; Gestion intégrée; Integrated Management Software Packages; Métier de comptable; OHADA; Progiciel; Standardized Accounting

Le long processus d'élaboration du droit africain à travers l'exemple de l'acte uniforme sur les sociétés coopératives - Hiez, David (2013)

Comment assurer une information financière de qualité sous le système comptable OHADA ? - Bampoky, Boniface (2013)
The quality financial information is useful for forecasting, monitoring and the development of performance within a company, the effectiveness of the optimal investment choices, risk management, the economic policy choices. After more than a decade of implementation by business, OHADA Accounting System has not changed significantly, which does not mean absence of difficulties in its practical application. This article is the status of these difficulties.
Keywords: Accounting standards; Consolidation; Contrôle interne; Internal control; Normalisation comptable; SYSCOHADA; UEMOA

Multi-Membership and the Effectiveness of Regional Trade Agreements in Western and Southern Africa: A Comparative Study of ECOWAS and SADC - Afesorgbor, Sylvanus Kwaku; Van Bergeijk, Peter A. G. (German Development Economics Conference N°1, 2011)
Using a gravity model for 35 countries and the years 1995-2006 we estimate the impact of regional trade agreements in Africa (in particular ECOWAS and SADC) and compare this to the a benchmark of North South trade integration (Europe‟s preferential trade agreement). We find that  ECOWAS and SADC membership significantly increases bilateral trade flows (and by more than for example preferential trade agreements with the EU do),  SADC membership has a stronger impact compared to ECOWAS and  that the impact of multi-membership critically depends on the characteristics of the overlapping RTA We find a positive impact if an additional membership complements the integration process of the original RTA: overlapping memberships had a significant positive effect on bilateral trade within the ECOWAS bloc but it is insignificant for SADC.

The Role of International Economic Law in Africa - Obale, Offah Ako (Society of International Economic Law (SIEL) Inaugural Conference 2008, 2008)
International Economic law (IEL) has a specific role to play in a complex modern Africa. The underdeveloped state of trade law regimes in Africa is arguably a reflection and product of the low level of commercial activity. The reverse is equally true in that underdevelopment in commercial activity on the continent is a reflection and product of the minimal role played thus far by international economic law.
Keywords: AEC; Africa; African; African Economic Community (AEC); Doha; Globilisation; International Economic Law; OHADA; Trade law; WTO

Recentrage du cadre comptable, durcissement de l'environnement fiscal et persistance de la gestion des données comptables : Une étude du comportement des Petites et Moyennes Entreprises camerounaises - Ngantchou, Alexis (La comptabilité, le contrôle et l'audit entre changement et stabilité, 2008)
Dans cette communication, nous postulons l'hypothèse de la manipulation des données comptables comme stratégie de contournement adoptée par les PME dans un environnement fiscal répressif. Par rapport à l'environnement spécifique des PME camerounaises présenté, l'étude se situe quelques années après l'adoption d'un nouveau cadre comptable, en l'occurrence le système comptable OHADA. Deux conclusions importantes méritent d'être immédiatement présentées. En premier lieu et conformément aux prédictions de Watts et Zimmerman, la taille est un facteur susceptible de favoriser l'instrumentalisation des données comptables. En second lieu, le type d'activité exercé conditionne la capacité à manipuler les données.
Keywords: Aménagement du cadre comptable; Durcissement de l'environnement fiscal; Instrumentalisation des données comptables; PME

L'expérience internationale de la Cour commune de justice et d'arbitrage de l'OHADA - Kenfack Douajni, Gaston (2è Congrès de l'Association des Hautes juridictions de cassation ayant en partage l'usage du Français (AHJUCAF), 2007)
Issu des actes du deuxième congrès de l'Association des Hautes juridictions de cassation ayant en partage l'usage du Français (AHJUCAF), Monsieur Gaston Kenfack-Douajni expose le bilan des activités de la Cour commune de justice et d'arbitrage de l'Ohada, ainsi que les actions susceptibles de renforcer son efficacité.
Keywords: Indépendance; Justice; Magistrature; OHADA